Micromegas with GEM preamplification for enhanced energy threshold in low-background gaseous time projection chambers [version 2; peer review: 2 approved] - Óscar Pérez Lázaro; Igor García Irastorza; Héctor Mirallas Sánchez; Susana Cebrián Guajardo; Theopisti Dafni; Gloria Luzón Marco; Juan Antonio García Pascual; Juan Francisco Castel Pablo; Javier Galán Lacarra; David Díez Ibáñez; Alfonso Ortiz de Solórzano; Álvaro Ezquerro Sastre; et al. (Open Research Europe)
Background We develop the concept of a Micromegas readout plane with an additional GEM preamplification stage placed a few millimetres above it to increase the maximum effective gain of the combined readout. Methods We implement it and test it in realistic conditions for its application to low-background dark matter searches like the TREX-DM experiment. For this, we use a Micromegas of Microbulk type, built with radiopure materials. Results We report on GEM effective extra gain factors of about 90, 50 and 20 in 1, 4 and 10 bar of Ar-1%iC4H10. These results are obtained in a small test chamber allowing for systematic scanning of voltages and pressures. In addition, a TREX-DM full-scale set-up has also been built and tested, featuring a replica of the fully-patterned TREX-DM Microbulk readout. Conclusions The results here obtained show promise to lower the threshold of the experiment down to 50 eV ee , corresponding to substantially enhanced sensitivity to low-mass WIMPs.